Transformation of Education: Pattern of Integration of Science in Learning at UIN Antasari Banjarmasin - Hairul Hudaya; Mahyuddin Barni (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This research aims to analyze the pattern of integrating knowledge in learning at UIN Antasari Banjarmasin. It has become a core issue at State Islamic Religious Higher Education Institutions (PTKIN), especially after the status change of several Islamic higher education institutions from STAIN or IAIN to UIN. This status change has had significant consequences on the shift in the fields of study at UIN, which were originally focused solely on Islamic sciences and have been expanded to include general sciences, both social and natural sciences. Many issues remain unresolved regarding the implementation of knowledge integration in the faculties at UIN Antasari, ranging from policies on knowledge integration in learning, the patterns of knowledge integration practiced by lecturers, and the extent to which lecturers respond to research on knowledge integration. The patterns of knowledge integration employed by some lecturers in the learning process include relating or presenting Quranic verses and Hadiths in the teaching of general subjects, and relating or presenting general knowledge in the teaching of Islamic studies. The integration models include informative and complementary approaches. The method used in this research is qualitative descriptive, which involves capturing the state of institutions, communities, and other entities based on the facts found. The research findings indicate that the pattern of knowledge integration involves lecturers relating Quranic verses and Hadiths in the teaching of general subjects, and integrating general knowledge in the teaching of Islamic studies, as well as using informative and complementary models.